ANALYSIS OF THE TREND IN EXPORTS OF DRIED SEAWEED BY CV MESTA ALAM TO THE GLOBAL MARKET - Markhamah, Siti; Sudarmiatin, Sudarmiatin; Pratikto, Heri (LPPM Universitas Jambi, 2026)
This study aims to analyze the influence of seaweed production, exchange rates, and international prices on the export trend of CV Mesta Alam's dried seaweed to the global market. Indonesia as a maritime country has great potential in seaweed development, but national export trends show fluctuations. The study uses a quantitative approach with panel data regression analysis that combines time series data (2020-2024) and cross-section (three central provinces: East Java, NTT, and Southeast Sulawesi). The selection of the best model through the Chow and Lagrange Multiplier tests shows the Common Effect Model (CEM) as the most appropriate model. The results of the analysis prove that partially, seaweed production (X1) has a positive and significant effect on exports (t-count 2.747 > t-table, sig. 0.019). The exchange rate (X2) also has a positive and significant effect (t-count 3.026 > t-table, sig. 0.010). Meanwhile, international prices (X3) have no significant effect (t-count 0.246 < t-table, sig. 0.808). Simultaneously, the three variables significantly influence exports (F-count 6.303 > F-table, sig. 0.009). The Adjusted R Square value of 53.19% indicates that the production, exchange rate, and price variables are able to explain the variation in CV Mesta Alam's exports, while the remaining 46.81% is explained by other factors. This finding implies the need to increase production with guaranteed quality, utilize the momentum of Rupiah depreciation, and strengthen non-price competitiveness through certification and market diversification.